Termite resistance of potential forest plantation woods in Malaysia - J. Kenneth, Grace; Wong, Andrew H.H; Tome, C.H.M. (Forest Research Institute Malaysia, 1997)
The resistance of selected Malaysian grown woods to attack by aggressive subterranean termites was evaluated in four-week, no-choice laboratory tests with Coptotermes formosanus Shiraki (lsoptera: Rhinotermitidae), and in an accelerated four-week, in· ground field test at the Forest Research Institute Malaysia (FRIM). This is part of an on-going e~ort between FRIM and the University of Hawaii to document the termite resistance of timber species of potential value in plantation forestry in Malaysia. Several of these tree genera also occur in Hawaii, or could potentiaJly be of value as weJI in forestry efforts in the Hawaiian island. Woods included in the first stage of the project reported here are the heartwood of acacia (Acacia mangium), batai (Albi:.ia falcataria), casuarina pine ( Casuarina equisetifolia), sen tang (Auulirachta excelsa), Malaysian-grown teak ( Tectona grandis), and sapwood of the susceptible species of rubberwood (Hevea brasiliensis). Of these, casuarina pine proved most resistant to termite attack. Malaysian teak and sen tang demonstrated somewhat less, but still significant termite resistance in the laboratory evaluations and a high degree of resistance in the field test. Sen tang is a relatively pest-free tree of interest for plantation forestry, and was also quite toxic to termites. Acacia, batai and rubberwood were very susceptible to termite attack, and would require protection in the field and treatment of the resulting wood products.